2019
DOI: 10.1039/c9ay01005j
|View full text |Cite
|
Sign up to set email alerts
|

A novel method based on a Mask R-CNN model for processing dPCR images

Abstract: The flow of Mask R-CNN model for processing digital polymerase chain reaction (dPCR) fluorescence images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…These challenges make the conventional image processing method with the thresholding and segmentation (GTS) scheme ( Figure S4A ) inaccurate and require human supervision for error correction in handling digital assay images. Mu et al ( Gou et al 2019 ; Hu et al 2019 ) showed that the use of machine learning algorithms would provide promising solutions to significantly improve the accuracy of digital assay image processing. However, this approach is only applied for single-color images with a small number of microreactors (a few thousand) with 1080×1120 pixels, which is impractical for high-throughput analysis.…”
Section: Resultsmentioning
confidence: 99%
“…These challenges make the conventional image processing method with the thresholding and segmentation (GTS) scheme ( Figure S4A ) inaccurate and require human supervision for error correction in handling digital assay images. Mu et al ( Gou et al 2019 ; Hu et al 2019 ) showed that the use of machine learning algorithms would provide promising solutions to significantly improve the accuracy of digital assay image processing. However, this approach is only applied for single-color images with a small number of microreactors (a few thousand) with 1080×1120 pixels, which is impractical for high-throughput analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This gave superior performance. Mask R-CNN was initially applied to computer vision datasets such as common objects in context COCO [ 46 ] but has since been used in applications such as nuclei detection and recognition of target signals in digital polymerase chain reaction fluorescence images [ 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to a previously reported study (29), we greatly reduced the number of convolution layers and filters (depth of network) for high speed processing. Our algorithm employs much fewer labels and features required for imaging processing than those for other typical CNN applications, such as autonomous driving.…”
Section: Introductionmentioning
confidence: 98%
“…These challenges make the conventional image processing method with the thresholding and segmentation (GTS) scheme ( Figure S4A) inaccurate, thus requiring human supervision for error correction in handling digital assay images. Mu et al (29,30) showed that the use of machine learning algorithms would provide promising solutions to significantly improve the accuracy of digital assay image processing. However, this approach is only applied for single-color images with a small number of microreactors (a few thousand) with 1080×1120 pixels, which is impractical for high-throughput analysis.…”
Section: Introductionmentioning
confidence: 99%